A Multidimensional Muscle Quality Index in Severe Obesity: Relationships with Ageing, Adiposity, and Functional Performance - Anelise Sonza; Aline Faquin; Gabriella Tringali; Roberta De Micheli; Stefano Lazzer; Alessandro Sartorio (Journal of Clinical Medicine, 2026)
Background/Objectives: Traditional anthropometric indicators such as body mass index (BMI) may inadequately capture functional muscular impairment in obesity. To investigate a multidimensional composite muscle quality index (MQI) integrating relative strength and lower-limb functional power in adults with severe obesity. Methods: The study included 202 adults with severe obesity. The Composite MQI was calculated as the mean of standardized z-scores derived from handgrip strength (HG) normalized by fat-free mass (FFM) (HG/FFM) and sit-to-stand power (STS power) normalized by skeletal muscle mass (MM) (STS power/MM). Associations between the Composite MQI and demographic, anthropometric, and body composition variables were assessed using correlation analyses and multivariable linear regression. Participants were additionally stratified into quartiles of the Composite MQI to explore age-related differences. Results: The mean age of the study group was 44.9 ± 14.0 years, and the BMI was 42.5 ± 5.1 kg/m2. Age showed a moderate inverse association with the Composite MQI (r = −0.41, p < 0.001), whereas BMI showed no significant correlation (r = −0.09). In multivariable regression models adjusted for sex and BMI, increasing age remained independently associated with lower Composite MQI (β = −0.022, p < 0.001), whereas BMI was not independently associated with Composite MQI (p = 0.373). Men exhibited higher relative and absolute HG than women, although no significant sex differences were observed for STS power/MM. Quartile analyses showed lower Composite MQI values among older participants. Conclusions: Among adults with severe obesity, age was associated with lower values of a multidimensional Composite MQI, whereas BMI showed limited association within this population. A composite approach integrating relative strength and functional power may provide a more comprehensive characterization of muscle performance relative to muscle quantity than traditional anthropometric measures.